Female highlife performers in Ghana : expression, resistance, and advocacy - Amoah-Ramey, Nana Abena (Lexington Books, Rowman & Littlefield Publishing Group, Inc., 2018)
This book takes an ethnomusicological approach to demonstrate the historical importance of female performers of Highlife music in Ghana.